TIC Et Performances Des Élèves Maitres Des Ecoles Normales d’Instituteurs Au Niger - Ismaël, Aboubacar Yenikoye; Bouba, Adamou (European Scientific Journal, ESJ, 2018)
The present study attempts to analyze the relationship between the use of ICT on the one hand and the performance of master students (future primary school teachers) on the other hand. A sample of 400 master students from the teacher training colleges of seven (7) administrative regions of Niger (Tillabery, Niamey, Dosso, Maradi, Zinder, Tahoua and Agadez) was selected. Data were collected using a questionnaire and the government’s logbook. It has been postulated that the use of ICT by masters’ students, outside normal class hours, improves performance, both in terms of the annual average of students and practical internship grades preparing them for the teaching profession. The results indicate that 92% of respondents say that ICT improves their academic performance. However, the statistical analysis does not show a significant difference between the performances of those who use ICT outside their normal hours and those who do not use them.